Performance Analysis of 3DES Image Encryption Algorithm for Image Transmission Between Two Computers Over a Wifi Network - Nurcahyono, Muhammad Ilham; Suharto, Nugroho; Ardiansyah, Rizky; Wijayanti, Rieke Adriati (JURNAL JARTEL: Jurnal Jaringan Telekomunikasi, 2024)
In today's digital era, data security, especially digital images, has become very important because of the risk of interception and unauthorized access. This research focuses on the use of the 3DES encryption algorithm to secure digital images. Taking inspiration from previous research examining image encryption based on Advanced Encryption Standard (AES) and Rivest–Shamir–Adleman (RSA) algorithms, this research develops and tests the implementation of the 3DES algorithm in the context of digital image storage and transmission. The main focus is on analyzing the performance of the 3DES algorithm in sending images between two computers over a Wi-Fi network, evaluating its effectiveness in maintaining data security. In addition, performance aspects such as encryption time, decryption time, and transmission overhead are also observed to assess feasibility. This research makes an important contribution to the development of reliable data security solutions in the rapidly changing digital era, particularly for secure wireless image communication systems.